Kinetics of miR-122 expression in the liver during acute HCV infection. - Youkyung Choi; Hans-Peter Dienes; Kris Krawczynski (PLoS ONE, 2013)
The relationships among micro RNA-122 (miR-122) expression in the liver, hepatitis C virus (HCV) replication and hepatic damage were analyzed in three chimpanzees observed for 180 days after inoculation with HCV genotype 1a. Levels of miR-122 in the liver and serum were measured by real-time RT PCR in serial liver biopsies and serum samples. Hepatic miR-122 levels were normalized separately for each of three chimpanzees with small RNAs and microRNAs that are endogenous to the liver and are stably expressed. Two- to 4-fold rise in hepatic miR-122 levels was observed at the onset of HCV infection (the first 4 weeks) when HCV titers in the liver and serum increased rapidly in all three chimpanzees in concordance with in vitro data indicating the miR-122 significance for HCV replication. Between 10 to 14 weeks after inoculation, when hepatic and serum HCV RNA titers exceeded 3 logs and alanine aminotransferase (ALT) activity was elevated, hepatic miR-122 levels were in decline. Cumulative data derived from all three chimpanzees from 180 days of observation documented an inverse (negative) correlation between hepatic miR-122 and HCV RNA in the liver and serum and positive correlation between level of serum miR-122 and HCV replication. Subsequent rise of miR-122 level during HCV clearance and ALT normalization suggested a tri-phasic occurrence of the relationship among hepatic miR-122 expression, HCV replication and hepatic destruction, which was the most apparent in one chimpanzee but less evident in two other animals. In vivo kinetics of hepatic and serum miR-122, HCV replication and hepatic destruction reflects complexities of the virus-host interaction during the acute phase of HCV infection.